A prospective comparative study of urinary calcium creatinine ratio versus doppler study in predicting preeclampsia - Mounika, Murukuti; Haneesha, Pottipati; Kameswaramma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Hypertensive disorders represent the most common medical complication of pregnancy complicating 5 to 10% of all pregnancies. Several changes have already occurred before the development of clinical syndrome of preeclampsia. One such change occurs in renal function leading to hypo-calciuria. Thus, in present study, urinary calcium creatinine ratio (UCCR) and doppler study are tested as parameters to predict development of preeclampsia in asymptomatic pregnant woman and assessing better predictor among them. Methods: Hospital based prospective study. Randomly selected pregnant women meeting inclusion and exclusion criteria, will be subjected to detailed history including age, parity, duration of pregnancy, examination including general examination, abdominal examination, routine laboratory investigations, calculate UCCR and ultrasound with doppler study at less than 20 weeks. Results: Out of 100 women, 25 had UCCR<0.04 and out of which 14 developed pre-eclampsia. Among them 33 had abnormal pulsatility index (PI) at 11-14 weeks and out of which 24 developed pre-eclampsia. In those 100 women, 58 had abnormal PI at 16-20 weeks and out of which 23 developed pre-eclampsia. Conclusions: Our study shows that we can predict preeclampsia by screening in early weeks of gestation i.e., by uterine artery doppler during NT scan around 11 to 14 weeks and during TIFFA appointment around 16 to 20 weeks and by UCCR. This study shows doppler study prediction is more sensitive and specific compared to UCCR.